Firm Closure, Financial Losses and the Consequences for an Entrepreneurial Restart - Georg Metzger (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
Many entrepreneurs who close a business are actually willing to venture anew. However, to realize a restart is not only a matter of willingness on the part of the entrepreneur but also of its feasibility. Regarding the feasibility of a restart, the aspect of capital acquisition might be particularly precarious for renascent entrepreneurs since business closures are likely to come up with financial losses. Financial losses arising from business closure can befall various stakeholders : shareholders, banks and public institutions, or suppliers and other stakeholders. The major finding of this analysis is that financial losses due to business closure strongly influence the likelihood of entrepreneurial restart - yet only when losses are incurred by banks. Losses which are incurred privately by the entrepreneurs or by other stakeholders do not influence the restart likelihood. Entrepreneurs who would seek to continue their entrepreneurial career after a business closure would be well advised to avoid causing losses at banks.
Keywords: M13; L26; G33; 330; Firm closure; financial loss; restart; Liquidation; Schulden; Kredit; Unternehmer; Unternehmensgründung; Deutschland